Pola Rekrutmen, Seleksi, Pendidikan Dan Pelatihan Pengaruhnya Terhadap Pengembangan Karier Aparatur Sipil Negara Kejaksaan Tinggi Sumtera Selatan - Zamzam, Fazakkir; Marnisah, Luis; Zamzam, Fakhry (Universitas Indo Global Mandiri Palembang, 2020)
The research objective was to find out the results of the analysis of how the influence of recruitment, selection and education & training patterns both partially and simutaneously towards career development. The survey method applied research model, uses 165 samples from a population of 295 South Sumatra High Prosecutors' staff, using proportional random sampling Technical data analysis using descriptive statistics and inferential statistics. In this study, the type of data used is primary data and secondary data. Data collection techniques using questionnaires, interviews, observation and documentation. Testing the hypothesis through t test and F test using SPSS analysis tools The results of data processing using SPSS 23, using the t test that t count is 7.378> with t table 1.9764 and 0.00 <0.05 significance that there is a positive and significant pattern of recruitment on career development; that t count is 13,730> with t table 1.9764 and 0.00 <0.05 significance that there is a positive and significant selection effect on career development; that t count is 19.303> with t table 1.9764 and 0.00 <0.05 significance that there is a positive and significant effect of education & training on career development; and use the F test that F count is 142.310> with F table 2.6687 significance 0.00 <0.05 that there is a positive influence and a significant pattern of recruitment, selection and education & training together towards career development, with the magnitude of the coefficient of determination The remaining 74.6% is influenced by other variables. The conclusion of the study is that the pattern of recruitment, selection and education & training has a positive and significant effect on career development both partially and simultaneously. The strategy for career development of the State Civil Service of South Sumatra's High Apparatus is very much determined by the opportunity given by the institution to the apparatus to attend education & training. Â Keywords ; pattern of recruitment, selection, education & training, career development